Complement Factor C7 Contributes to Lung Immunopathology Caused by Mycobacterium tuberculosis - Kerry J. Welsh; Cole T. Lewis; Sydney Boyd; Michael C. Braun; Jeffrey K. Actor (Clinical and Developmental Immunology)
Mycobacterium tuberculosis (MTB) remains a significant global health burden despite the availability of antimicrobial chemotherapy. Increasing evidence indicates a critical role of the complement system in the development of host protection against the bacillus, but few studies have specifically explored the function of the terminal complement factors. Mice deficient in complement C7 and wild-type C57BL/6 mice were aerosol challenged with MTB Erdman and assessed for bacterial burden, histopathology, and lung cytokine responses at days 30 and 60 post-infection. Macrophages isolated from C7 −/− and wild-type mice were evaluated for MTB proliferation and cytokine production. C7 −/− mice had significantly less liver colony forming units (CFUs) at day 30; no differences were noted in lung CFUs. The C7 deficient mice had markedly reduced lung occlusion with significantly increased total lymphocytes, decreased macrophages, and increased numbers of CD4+ cells 60 days post-infection. Expression of lung IFN-γ and TNF-α was increased at day 60 compared to wild-type mice. There were no differences in MTB-proliferation in macrophages isolated from wild-type and knock-out mice. These results indicate a role for complement C7 in the development of MTB induced immunopathology which warrants further investigation.